PENGARUH PRAKTIK KOLABORATIF TERHADAP PENGEMBANGAN KEWIRAUSAHAAN PEREMPUAN - Komang Sri Lestari, Titis Tatasari, Nabila Anjani Faradiba Agustin (Social Sciences Journal, 2025)
This research explores the impact of collaborative practices on women entrepreneurs who often face structural challenges such as limited access to capital, training and social networks that can hinder their business development. Collaboration between women entrepreneurs can create opportunities for a wider range of resources, knowledge and market access. This research uses a qualitative approach with in-depth interviews and case studies of women entrepreneurs involved in various forms of collaboration. The findings of this study show that both formal and informal collaborative practices have a positive impact on women's business development, both in terms of improving skills, access to capital, and expanding social networks. In addition, things like work culture, perceptions of collaboration and government policy support play an important role in the success of collaboration. The results of this collaboration are expected to help policy makers and organizations that support women's empowerment develop better collaboration capital and provide new insights into how collaboration can achieve goals. Keywords - Collaborative Enterprises; Women's Empowerment; Structural Challenges